A Novel Hybrid Negative Half Cycle Biased Modulation Scheme for Cascaded Multilevel Inverter - R. Hemanthakumar; V. RaghavendraRajan; C.S. Ajin Sekhar; M. Sasikumar (Institute of Advanced Engineering and Science, 2014)
This paper proposes a new Modified hybrid modulation scheme for cascaded multilevel inverter. The proposed method employs novel single carrier sinusoidal pulse width modulation with its negative cycle biased (HNHCBM) for reducing switching losses when compared to other sinusoidal modulation methods using a hybrid scheme. This scheme is a derivative of various single carrier sinusoidal pulse width modulation scheme and main advantages are reduced harmonics, enhanced output voltage, reduced power loss in the series cells and ease of implementation. The simulation results are analysed with matlab/simulink and compared with experimental results obtained using DSP processor TMS320F2407 by applying it to 5-level inverter and the results are summarized.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5696